PENGARUH KONSENTRASI LARUTAN KAPUR (Ca(OH)2) DAN LAMA PEREBUSAN TERHADAP MUTU TORTILLA JAGUNG - Vita Novalina Lawalata; Tanudin Tanudin; Cynthia G C Lopulalan (AGRITEKNO: Jurnal Teknologi Pertanian, 2017)
The objective of this study was to analyze the effects of the concentration of caustic lime solution and boiling time on the quality of tortilla corn chips made from mature corn. A completely randomized factorial experimental design was applied in this study. Two factors were assigned including concentration of caustic lime solution (3, 4, and 5%) and boiling time (30, 60, and 90 minutes). Observed variables were both chemical properties (moisture, ash, protein, fat, and carbohydrate). Results showed that the interaction between concentration of caustic lime solution and boiling time did not have significant effect on protein and fat content of the tortilla. The main effect of a single factor boiling time mostly influenced many observed variables particularly the organoleptic properties of the tortilla. The concentration of caustic lime solution of 4% and boiling the corn for 30 minutes was the best interaction to produce tortilla having the best quality with moisture, ash, and carbohydrate contents of 5.53%, 7.59%, and 67.96%, respectively. Keywords: corn, tortillas, lime, boiling, chemical composition, organoleptic ABSTRAK Tujuan penelitian ini adalah untuk menganalisa pengaruh konsentrasi larutan kapur dan lama perebusan terhadap mutu tortilla jagung dari pemanfaatan jagung tua. Rancangan yang digunakan adalah Rancangan Acak Lengkap Faktorial dengan faktor konsentrasi larutan kapur (3%, 4%, dan 5%) dan faktor lama perebusan (30 menit, 60 menit, dan 90 menit). Peubah yang diamati adalah sifat kimia (kadar air, kadar abu, protein, lemak dan karbohidrat by different). Hasil penelitian menunujukan bahwa pengaruh larutan kapur dan lama perebusan menghasilkan kandungan protein dan lemak tidak nyata dalam interaksinya. Perlakuan dengan lama perebusan tortilla jagung lebih mempengaruhi peubah-peubah yang diamati terutama pada uji organoleptik rasa tortilla jagung. Interaksi terbaik pada konsentrasi larutan kapur 4% dan lama perebusan 30 menit, menghasilkan mutu tortilla jagung dengan kadar air 5,53%, kadar abu 7,59% dan kadar karbohidrat by different 67,96%. Kata kunci: jagung, tortilla, kapur, perebusan, komposisi kimia, organoleptik